Menemukan Peran Anak dalam Rangka Proses Pengajaran Firman Tuhan - Detrianus Zai; Salomo Sihombing; Pelita Hati Surbakti (Te Deum (Jurnal Teologi dan Pengembangan Pelayanan), 2025)
This article aims to examine the role of children more deeply by analyzing Deuteronomy 6:1-9 through a qualitative method with a narrative analysis approach. The study reveals that Deuteronomy 6:1-9 not only commands parents to teach their children, but also implies the active involvement of children as part of the people of Israel who listen to, receive, and internalize the teachings in daily life. The use of visual symbolism and verbal repetition in the text emphasizes the importance of holistic and contextual teaching. Children are seen as functional characters in the narrative not merely passive recipients, but active inheritors and participants in the practice of God's Word. Therefore, the findings of this study broaden the perspective on the role of children in Christian spiritual education and invite both churches and parents to design learning strategies that empower children as active subjects in the teaching of God's Word.